Patient selection for CAR T or BiTE therapy in multiple myeloma: Which treatment for each patient? - Kegyes, David; Constantinescu, Catalin; Vrancken, Louise; Rasche, Leo; Gregoire, Celine; Tigu, Bogdan; Gulei, Diana; Dima, Delia; Tanase, Alina; Einsele, Hermann; Ciurea, Stefan; Tomuleasa, Ciprian; et al. (Journal of Hematology & Oncology, 2022)
Multiple myeloma (MM) is a plasma cell malignancy that affects an increasing number of patients worldwide. Despite all the efforts to understand its pathogenesis and develop new treatment modalities, MM remains an incurable disease. Novel immunotherapies, such as CAR T cell therapy (CAR) and bispecific T cell engagers (BiTE), are intensively targeting different surface antigens, such as BMCA, SLAMF7 (CS1), GPRC5D, FCRH5 or CD38. However, stem cell transplantation is still indispensable in transplant-eligible patients. Studies suggest that the early use of immunotherapy may improve outcomes significantly. In this review, we summarize the currently available clinical literature on CAR and BiTE in MM. Furthermore, we will compare these two T cell-based immunotherapies and discuss potential therapeutic approaches to promote development of new clinical trials, using T cell-based immunotherapies, even as bridging therapies to a transplant.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Adoptive cell therapy; BAT; Bispecific antibody; Bispecific antibody armed T cell; Bispecific T cell engager; BiTE; CAR T; Chimeric antigen receptor; Immunotherapy; Multiple myeloma; Stem cell transplantation